Опис гістерезисних характеристик сферичних шарнірів просторової системи приводів з врахуванням стохастичної невизначеності - Струтинський, Сергій; Рибак, Лариса (КІНПАТРІ ЛТД, 2013)
The characteristics of the space of spherical joints of the drive system. Was presented for analytical description of the characteristics of the used methods of the theory of fuzzy sets. Methods of finding the characteristic functions of the fuzzy sets describing the characteristics of the joints. Methods take into account random variations in the characteristics of joints.
Description of hysteresis descriptions of spherical hinges of spatial system of occasions is taking into account stochastic vagueness